Introduction to data acquisition with LabView - King, Robert H. (McGraw-Hill Companies, 2008)
LabVIEW (short for Laboratory Virtual Instrumentation Engineering Workbench) is a program development application, much like C or FORTRAN. LabVIEW, is however, different from those applications in one important respect. Other programming systems used text-based languages to create lines of code, while LabVIEW uses a graphical programming language, G, to create programs in block diagram form. King's Introduction to Data Acquisition with LabVIEW is a comprehensive, up to date text that can be purchased with or with out the LabVIEW software.